MdBAM17, a novel member of the β-amylase gene family, positively regulates starch degradation in ALA-induced stomatal opening in apple - Longbo Liu; Jiayi Zhou; Jianting Zhang; Yan Zhong; Liangju Wang (Horticultural Plant Journal)
5-Aminolevulinic acid (ALA) is a novel plant growth regulator that has shown outstanding capability to promote stomatal opening. Starch degradation, catalyzed by β-amylase (EC3.2.1.2, BAM), plays an important role in stomatal opening. However, whether the starch breakdown is involved in ALA-regulating stomatal movement is unclear. In the current study, we found that exogenous ALA effectively stimulated the starch breakdown in guard cells, increased β-amylase activity and promoted stomatal opening in leaves of apple (Malus × domestica). Based on genome-wide identification, we identified a total of 119 members of BAM gene family in ten commonly Rosaceae crops. Analyses of gene structure, motif identification, and gene pair collinearity revealed relative conservation among members within the same group or subgroup. Among these genes, MdBAM17 and other 12 genes were identified as the orthologous genes of AtBAM1, which is responsible for starch degradation to modulate the stomatal movement in Arabidopsis. qRT-PCR analysis revealed a positive correlation between the expressions of MdBAM17 and stomatal aperture, as well as β-amylase activity, whereas a negative correlation was observed with the starch content. Subcellular localization analysis confirmed that MdBAM17 is a chloroplast protein, consistent with the AtBAM1. MdBAM17 was mainly expressed in guard cells and responsive to exogenous ALA. Overexpressing MdBAM17 increased β-amylase activity and promoted starch breakdown, leading to stomatal opening, which was further strengthened by ALA. RNA-interfering MdBAM17 decreased β-amylase activity, resulting in starch accumulation, and impairing the stomatal opening by ALA. However, modulation of MdBAM17 expression did not affect the levels of flavonols and H2O2 in guard cells, suggesting that MdBAM17-promoted starch degradation may function at downstream of ROS signaling in the ALA-regulated stomatal opening. Our findings provide new insights into the mechanisms of ALA-regulated stomatal movement.